Comparing social representation of water quality in coastal lagoons with normative use of ecological indicators. (March 2019) - Audouit, Christelle; Pasqualini, Vanina; De Wit, Rutger; Flanquart, Hervé; Deboudt, Philippe; Rufin-Soler, Caroline
Abstract: Coastal lagoons are important for coastal and marine biodiversity. Nevertheless, they are very sensitive and vulnerable to human impacts, which often result in a decrease of their biodiversity and degradation of their water quality. Considering recent efforts for ecological restoration of coastal lagoons, it appears appropriate to compare the social representations of users of the coastal lagoons and of inhabitants, with ecological diagnoses of biodiversity and water quality. The main question is whether there is congruence between water quality defined by environmental criteria on one hand and the social representations of these issues by lagoon users and local populations on the other hand? How can we explain the social representations of lagoons concerning landscape, water quality and biodiversity? This study was focused on two Mediterranean lagoon areas, i.e., the Palavas lagoon complex (Gulf of Lions) and Biguglia lagoon (Corsica). We have documented these changes of ecosystem states using the criteria of regional monitoring programs that anticipated the implementation of the Water Framework Directive (WFD). Accordingly, both systems have shown bad water quality in the past with recent improvements. For studying the social representations, we conducted 267 surveys with lagoon inhabitants that live close to the lagoons and users of these spaces. In general, most of the residents living close to the lagoons considered that water quality is moderate to good, that biodiversity is good to high and that the current situation is better than in the past. However, some discrepancies between social representations and ecological diagnoses were observed.